Odpowiedzi

2010-04-06T13:14:04+02:00
1.
A
a) Df: xε <-2, 5>
b) Zw: <-3, 1>
c) Wartości ujemne: xε <-2, 3)
d) Wmax= 1, Wmin= 3
e) Mo: x={3}

B
a) Df: x={-7, -5, -3, 0, 2}
b) Zw: {0, -2, 0, 12, -8}
c) Wartości ujemne: x={-5, 2}
d) Wmax= 12 , Wmin= -8
e) Mo: x={-7, -3}

C
a) Df: x={-4, 0, 3, 5, 9}
b) Zw: {-2, 0}
c) Wartości ujemne: x={-4, 0, 3}
d) Wmax= 0 , Wmin= -2
e) Mo: x={5, 9}
--------------------------------------------------------------------------
2.
f-: xε (-∞, 0>; <6, 8>
f+: xε <3, 6>
f=: xε <0, 3>; <8, +∞)
--------------------------------------------------------------------------
3.
a)
y=(2x-3)/(3x-2)
3x-2 ≠ 0
3x ≠ 2
x ≠ 2/3
Df: R/{2/3}

b)
y=√5x+1
5x+1 ≥ 0
5x ≥ (-1)
x ≥ -(1/5)
Df: R/{-(1/5)}
--------------------------------------------------------------------------
4.
y=(1+√x)/(1-x²)

1-x² ≠ 0 √x ≥ 0
-x² ≠ -1 x ≥ 0
x² ≠ 1
x ≠ 1 ∨ (-1)
Df: xε <0, 1) ∨ (1, +∞)

A
(1+3)/(1-81) = -(1/2)
4/(-80) = -(1/2)
-(1/20) ≠ -(1/2)
L≠P

B
x=1 (1 nie należy do dziedziny funkcji)

C
(1+0)/(1-0) = 1
1/1 = 1
1 = 1
L=P

Tylko punkt C należy do wykresu funkcji.
--------------------------------------------------------------------------
5.
http://i39.tinypic.com/15x4o48.jpg
--------------------------------------------------------------------------
6.
a)
Df: xε <-4, -2>; (-1, 2); <2, 5)
Zw: <-2, 3)

b)
xε <-4, 2); (0, 2); <2, 5>
Tak, jest nią {-2}
--------------------------------------------------------------------------
7.
a)
y=(x+5)/(x²-2x+3)
alternatywnie:
------------------------
y=(x+5)/((x-2)x+3)
------------------------
x-2 ≠ 0 ∨ x+3 ≠ 0
x ≠ 2 ∨ x ≠ -3
Df: R/{-3, 2}

b)
y=(√3-x)/(x+4)
x+4 ≠ 0 ∨ 3-x ≥ 0
x ≠ -4 ∨ -x ≥ -3
x ≤ 3
Df: xε (-∞, -4) ∨ (4, 3>
--------------------------------------------------------------------------
8.
http://i42.tinypic.com/2hf26gm.jpg
--------------------------------------------------------------------------
9.
http://i40.tinypic.com/4t7j2r.jpg
--------------------------------------------------------------------------
10.
a)
W+
f: xε (-3, 0>
g: xε <-4, -1) ∨ (1, 4>

W=
x= {-2, 2}

Wf > Wg:
xε (-2, 2)

b)
W+
f: xε (-∞, 4>
g: xε (3, 4>

W=
x= {-1, 3}

Wf > Wg:
xε (-∞, 1) ∨ (3, 4>

c)
W+
f: xε (-3, 1) ∨ (1, 4>
g: xε <4, 1) ∨ <1, 4>

W=
x= {-2, 0, 2, 4}

Wf > Wg:
xε (-2, 1) ∨ (0, 1) ∨ (2, 4)